(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This thesis discusses the relevance of the linguistic image of the world in modern society. It explores how languages reflect and shape the worldview of their speakers, embedding cultural values, historical experiences, and patterns of thought. The study highlights the significance of understanding linguistic worldviews in translation, intercultural communication, and language education. By examining how different languages conceptualize reality, the paper emphasizes the role of language in shaping identity and promoting mutual understanding in a globalized world.